2011
DOI: 10.1089/scd.2010.0349
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Nutrition Modulates Muscle Stem Cell Number: Implications for Muscle Mass and Repair

Abstract: Suboptimal nutrition during prenatal and early postnatal development is associated with increased risk for type 2 diabetes during adult life. A hallmark of such diabetes risk is altered body composition, including reduced lean mass and increased adiposity. Since stem cell number and activity are important determinants of muscle mass, modulation of perinatal nutrition could alter stem cell number/function, potentially mediating developmentally programmed reductions in muscle mass. Skeletal muscle precursors (SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 43 publications
(60 reference statements)
5
73
3
1
Order By: Relevance
“…In vivo studies of LBW subjects support the idea of fundamental changes in lipid metabolism including increased fasting lipolysis (20) as well as increased nocturnal fat oxidation, potentially associated with an inability to retain fat in the subcutaneous adipose tissue depot (45). A previous study reported reduced numbers of muscle satellite stem cells in mice subjected to prenatal undernutrition (46). Indeed, in vivo fat tissue preadipocyte number could also theoretically be altered and thereby contribute to the increased risk of T2D in LBW subjects (46).…”
Section: Discussionmentioning
confidence: 72%
“…In vivo studies of LBW subjects support the idea of fundamental changes in lipid metabolism including increased fasting lipolysis (20) as well as increased nocturnal fat oxidation, potentially associated with an inability to retain fat in the subcutaneous adipose tissue depot (45). A previous study reported reduced numbers of muscle satellite stem cells in mice subjected to prenatal undernutrition (46). Indeed, in vivo fat tissue preadipocyte number could also theoretically be altered and thereby contribute to the increased risk of T2D in LBW subjects (46).…”
Section: Discussionmentioning
confidence: 72%
“…Finally, Nur77's dual role in regulating metabolism and muscle mass raises intriguing questions regarding the interdependence of these two processes. Based on studies examining the impact of nutrition on muscle stem cell function (63,64), we posit that Nur77 coordinates the cross talk between myogenesis and metabolism. Future studies examining the interplay between Nur77, glycolysis, and myogenesis will provide valuable insights into the relationship between metabolism and function, with important implications for conditions such as diabetes and muscle wasting.…”
Section: Fig 10mentioning
confidence: 99%
“…The release of several key growth factors, such as insulin-like growth factor (IGF) and hepatocyte growth factor (HGF), at the site of injury helps to control muscle regeneration by regulating the proliferation and differentiation of satellite cells (Yablonka-Reuveni et al 2008).…”
Section: Molecular and Cellular Regulators Of Satellite Cell-mediatedmentioning
confidence: 99%
“…In addition, reflecting the fact that skeletal muscle serves as a major site for glucose storage and insulin uptake, playing a crucial role in overall body metabolism, recent studies indicate that nutrient-dependent changes in satellite cell populations may also modulate stem cell function and homeostasis during aging (Hu et al 2010). For example, diabetic patients can experience delayed healing of injured muscle or limited recovery from skeletal muscle trauma (Gulati and Swamy 1991;Vignaud et al 2007), and recent evidence suggests that excess nutrient intake is associated with defective muscle stem cell function (Woo et al 2011). Conversely, calorie restriction (CR), which extends life span and delays the onset of many age-related diseases in multiple species, appears to preserve stem cell function with age in the hematopoietic system (Ertl et al 2008), and may similarly enhance the regenerative potential of aged satellite cells.…”
mentioning
confidence: 99%